2018
DOI: 10.3390/w10030276
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Assessment of Risks from Drinking and Recreational Water Exposure to Children in the State of New Jersey

Abstract: Abstract:In this study, we conducted a worst-case risk assessment for children's health from ingestion exposure to water sources in two densely populated counties of the Piedmont province of New Jersey-Hunterdon and Mercer counties. Carcinogenic and non-carcinogenic health risk estimates for 19 contaminants, representing 3 different chemical classes-organic, inorganic and contaminants of emerging concern (CEC), for which environmental monitoring data are available-were generated. The three exposure scenarios e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Their further study indicated that the carcinogenic risk, non-carcinogenic risk and total health risk caused by these pollutants in three water bodies ranked from high to low as source water > tap water > finished water [3]. Owen et al [4] conducted a risk assessment of children's health in two counties in New Jersey, the United States. Based on environmental monitoring data, the carcinogenic and non-carcinogenic risks of 19 pollutants in three categories of organic matter, inorganic matter and emerging pollutants were evaluated.…”
Section: Health Risk Assessment Of Micropollutantsmentioning
confidence: 99%
“…Their further study indicated that the carcinogenic risk, non-carcinogenic risk and total health risk caused by these pollutants in three water bodies ranked from high to low as source water > tap water > finished water [3]. Owen et al [4] conducted a risk assessment of children's health in two counties in New Jersey, the United States. Based on environmental monitoring data, the carcinogenic and non-carcinogenic risks of 19 pollutants in three categories of organic matter, inorganic matter and emerging pollutants were evaluated.…”
Section: Health Risk Assessment Of Micropollutantsmentioning
confidence: 99%